El personaje gay : un acercamiento crítico desde la perspectiva de género, los estudios gay y la teoría queer en seis cuentos mexicanos - Villegas Martínez, Víctor Saúl (Pública crítica ;, 2018)
Analyzes evidence in late 20th century fiction of social changes that have occurred in Mexico regarding sexuality and gender. Identifies characters created to embody ideas of body, desire, social norms and transgression in stories by Jorge Arturo Ojeda, Luis González de Alba, Inés Arredondo, Luis Zapata, Enrique Serna and José Joaquín Blanco. Edition limited to 500 copies.